School-Based Malaria Screening and Treatment Reduces Plasmodium falciparum Infection and Anemia Prevalence in Two Transmission Settings in Malawi . (15th March 2022) - Cohee, Lauren M; Peterson, Ingrid; Buchwald, Andrea G; Coalson, Jenna E; Valim, Clarissa; Chilombe, Moses; Ngwira, Andrew; Bauleni, Andy; Schaffer-DeRoo, Sarah; Seydel, Karl B; Wilson, Mark L; Taylor, Terrie E; et al.
Abstract: Background: In areas highly endemic for malaria, Plasmodium falciparum infection prevalence peaks in school-age children, adversely affecting health and education. School-based intermittent preventive treatment reduces this burden but concerns about cost and widespread use of antimalarial drugs limit enthusiasm for this approach. School-based screening and treatment is an attractive alternative. In a prospective cohort study, we evaluated the impact of school-based screening and treatment on the prevalence of P. falciparum infection and anemia in 2 transmission settings. Methods: We screened 704 students in 4 Malawian primary schools for P. falciparum infection using rapid diagnostic tests (RDTs), and treated students who tested positive with artemether-lumefantrine. We determined P. falciparum infection by microscopy and quantitative polymerase chain reaction (qPCR), and hemoglobin concentrations over 6 weeks in all students. Results: Prevalence of infection by RDT screening was 37% (9%–64% among schools). An additional 9% of students had infections detected by qPCR. Following the intervention, significant reductions in infections were detected by microscopy (adjusted relative reduction [aRR], 48.8%; P  < .0001) and qPCR (aRR, 24.5%; P  < .0001), and in anemia prevalence (aRR, 30.8%; P  = .003). Intervention impact was reduced by infections not detected by RDT and new infections following treatment. Conclusions: School-based screening and treatment reduced P. falciparum infection and anemia. This approach could be enhanced by repeating screening, using more-sensitive screening tests, and providing longer-acting drugs. Clinical Trials Registration: NCT04858087. Abstract : In this cohortstudy of primary school students in 2 malaria transmission settings, school-based screening and treatment was associated with decreased prevalence of Plasmodium falciparum infection and anemia. Impact was reduced by infections not detected and new infections following treatment.